2020
DOI: 10.1371/journal.pone.0230895
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of smoking cessation, coffee and bread consumption on the intestinal microbial composition among Saudis: A cross-sectional study

Abstract: The gut microbiota is often affected by the dietary and lifestyle habits of the host, resulting in a better efficacy that favors energy harvesting from the consumed food. Our objective was to characterize the composition of gut microbiota in adult Saudis and investigate possible association with lifestyle and dietary practices. Feces from 104 Saudi volunteers (48% males) were tested for microbiota by sequencing the V3-V4 region of bacterial 16S ribosomal RNA (rRNA). For all participants, data were collected re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 40 publications
0
34
1
Order By: Relevance
“…Of the 32 included studies, 25 studies investigated alpha diversity in obese versus non-obese adults, two did not assess alpha diversity, and five studies did not report alpha diversity stratified by BMI ( Table 2 ). At the individual study level, results on the difference in alpha diversity between obese and non-obese persons were discrepant ( Figure 3 ): the Shannon index, reported in 22 studies, was found to be significantly lower in obese compared to non-obese adults in nine studies [ 17 , 32 , 35 , 37 , 41 , 46 , 48 , 51 , 54 ], higher in two studies [ 21 , 54 ], and not significantly different in eleven studies [ 19 , 33 , 34 , 35 , 39 , 44 , 45 , 47 , 49 , 52 , 53 ]. The study of Salah et al [ 54 ] found significantly lower diversity (Shannon index) among obese as compared to non-obese persons and higher diversity among obese diabetic compared to non-obese persons.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 32 included studies, 25 studies investigated alpha diversity in obese versus non-obese adults, two did not assess alpha diversity, and five studies did not report alpha diversity stratified by BMI ( Table 2 ). At the individual study level, results on the difference in alpha diversity between obese and non-obese persons were discrepant ( Figure 3 ): the Shannon index, reported in 22 studies, was found to be significantly lower in obese compared to non-obese adults in nine studies [ 17 , 32 , 35 , 37 , 41 , 46 , 48 , 51 , 54 ], higher in two studies [ 21 , 54 ], and not significantly different in eleven studies [ 19 , 33 , 34 , 35 , 39 , 44 , 45 , 47 , 49 , 52 , 53 ]. The study of Salah et al [ 54 ] found significantly lower diversity (Shannon index) among obese as compared to non-obese persons and higher diversity among obese diabetic compared to non-obese persons.…”
Section: Resultsmentioning
confidence: 99%
“…From a total of 2445 unique hits, 116 studies were selected for full-text review. Of these, 33 primary reports [ 17 , 18 , 19 , 20 , 21 , 32 , 33 , 34 , 35 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ], including 32 studies met the criteria for inclusion and were selected for data extraction and synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, drinking coffee is accompanied by an elevated relative abundance of gut microbiota such as Fusobacteria and Bacteroides thetaiotaomicron. 19 Second, caffeine, the main active ingredient in coffee, can directly promote the secretion of small intestinal fluid 20 and indirectly decrease fluid absorption by promoting the secretion of intestinal anions such as chloride through a variety of pathways. 21,22 It is interesting and worth exploring why a further increase in drinking coffee does not lead to an increased prevalence of FBD.…”
Section: Discussionmentioning
confidence: 99%